TERRORISM AS CORE INTERNATIONAL CRIMES : THE CASE OF FOREIGN TERRORIST FIGHTER (FTF) OF ISLAMIC STATE OF IRAQ AND SYRIA (ISIS) - Angela Jessica Desmonda; Diajeng Wulan Christianti (International Law Department, Faculty of Law Universitas Padjadjaran, 2022)
Since it had established a caliphate in 2014, Islamic State of Iraq and Syria (ISIS) continued to threaten the international peace and security by attacking and killing civilians. ISIS foreign terrorist fighters (FTFs) are ISIS members who have combat functions. Altough it is a serious crime, terrorism has not yet been recognized as a stand-alone core international crimes according to customary international law. The fact that ISIS is referred to as a terrorist groups, not a state-entity, has also raised a question of whether ISIS FTFs can only be prosecuted for committing terrorism related offences. This paper argues that terrorism acts by ISIS FTFs can fit the element of the existing core international crimes such as crimes against humanity, war crimes and genocide To this end, this paper elaborates the most common offences committed by ISIS FTFs and analyses element of each of core international crimes. This paper concludes that ISIS FTFs should be held liable for those core international crimes and prosecuted before national and international criminal court accordingly.